Distribution characteristics of reservoir fluid properties in Cuu Long basin - Hung, Nguyen Manh; Tien, Hoang Dinh; Ky, Nguyen Viet (Vietnam Journal of Marine Science and Technology, 2019)
Oil and gas have been discovered and produced from Cuu Long basin for more than 20 years however the distribution charateristics according to stratigraphy have not been studied. In this study, data from more than 200 PVT reports of more than 30 discoveries and published reports of previous studies were investigated to find out the distribution characteristics of reservoir fluid properties. The results show that oil and gas in Cuu Long basin mainly follow normal distribution, in some areas they are in redistribution (retrogradation) stage. Saturation pressure, GOR and compressibility are very high at the centre area and rapidly reduce at the margin area, whereas reservoir fluid density is in the inverse trend. Oil and gas have tendency to accumulate in NW-SE direction. Condensate discoveries in Cuu Long basin mainly result from redistribution process except some discoveries in center of basin.